Coaches, peers and parents’ autonomy support and its predictive capacity on young athletes’ self-determined motivation - Ramis, Yago; Torregrosa, Miquel; Viladrich, Carme; Cruz, Jaume (Anales de Psicología / Annals of Psychology, 2013)
The purpose of this study was to explore the influence of youth sports’ socialization agents on athletes’ self-determined motivation. We used a transversal methodology and assessed, via questionnaires, the predictive capacity of coaches, peers and parental autonomy support on autonomous regulation, controlled regulation and amotivation of 269 athletes age ranged between 11 and 17 years old, through regression analyses. Results showed that the perception of coaches’ autonomy support in first place, followed by parental and peers’, predicted a more autonomous behavioral regulation. The perception of coaches’ autonomy support also played the role of protective factor for the athletes’ amotivation. Our discussion, in line with Vallerand’s hierarchical model, suggests that in a specific context such as sports, the most influent autonomy support would be provided by the most authoritative figure in that given context, specifically coaches for this case.